If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + -5 = -41 + p Reorder the terms: -5 + 5p = -41 + p Solving -5 + 5p = -41 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -5 + 5p + -1p = -41 + p + -1p Combine like terms: 5p + -1p = 4p -5 + 4p = -41 + p + -1p Combine like terms: p + -1p = 0 -5 + 4p = -41 + 0 -5 + 4p = -41 Add '5' to each side of the equation. -5 + 5 + 4p = -41 + 5 Combine like terms: -5 + 5 = 0 0 + 4p = -41 + 5 4p = -41 + 5 Combine like terms: -41 + 5 = -36 4p = -36 Divide each side by '4'. p = -9 Simplifying p = -9
| 8(4k-4)=-54k-32 | | 5x^2-2=9x | | -9=19(h-3) | | 4=0.2(r-0.08) | | x+.0875x=9 | | 5x+3-2x=-15 | | 6(x-4x)= | | 6z+4=z-2 | | 2n-1-3n=5n-7-3n | | 0.2t+.833=.666-t | | -.555x+.333=.222 | | 5.5x-4.5=6.5 | | -2(t-2)+4t=9t-9 | | -(7y+4)-(2y-5)=14-(5y-3) | | 8.6x+80.26=-11.4x+78.62 | | 8.6+80.26=-11.4+78.62 | | 10y-1-4y+8= | | 10-2b-3b=20 | | 3(x-2)-(x+6)=4(x-1) | | (2(x^2)+2)= | | (4y)(4y)= | | (M^0)(-4)= | | 3+2(x-7)=x-18 | | 24a^4-4a^4= | | -(u-w)-6(-3w-6u)= | | 6x^6-60x^5-144x^4= | | 45x-5=546 | | 6(3z-1)-5(z+5)=10(z+1) | | 5(z-4)+4z=5-6z | | 3x^2-25x+36=0 | | O(9)=2(9)-1 | | x^2=-112 |